Penerapan Asas Keseimbangan Dalam Perjanjian Kerja sama Penyediaan Layanan Sebelum Penerbangan - Furcony Putri Syakura; Fauzie Yusuf Hasibuan; Sulhan Sulhan (Postgraduate of Jayabaya University, 2018)
The Cooperation Agreement of Provision of Pre-Flight Services is signed by the Secretary General of the House of Representatives of the Republic of Indonesia (as The First Party and the Service User) and the Director of Operations of PT Garuda Indonesia Tbk (as The Second Party and the Service Provider). The principle of proportionality becomes very important in this Cooperation Agreement with an assumption that if the positions of the rights and obligations of The Parties in this agreement are equal then it is felt fair by both parties. The study was conducted by using Normative Juridical method. In writing this thesis, the author examines the Document of Cooperation Agreement of Provision of Pre-Flight Services Between the Secretariat General of the House of Representatives of the Republic of Indonesia and PT Garuda Indonesia (Persero) Tbk Year 2016, in particular the rights and obligations of The Parties contained in Article 7 and Article 8. The author also conducted interview to the service user, service provider and experts in the agreement field. Based on researcher’s analysis, the implementation of the Cooperation Agreement of Provision of Pre-Flight Services is not equal so it is unfair. If the Cooperation Agreement is to be extended for the Year 2018, it is recommended to the Secretariat General of the House of Representatives of the Republic of Indonesia to renegotiate Article 7 and Article 8 which regulate the rights and obligations of The Parties so that it can be reviewed and modified based on what is expected.